Small-molecule inhibitors at the PSD-95/nNOS interface protect against glutamate-induced neuronal atrophy in primary cortical neurons. (20th August 2015) - Doucet, M.V.; O'Toole, E.; Connor, T.; Harkin, A.
Highlights: Excess NMDA and NO decrease neurite outgrowth of cultured rat primary cortical neurons. NMDA-R antagonists and nNOS inhibitors can protect against these effects. Novel small molecule inhibitors of the PSD-95/nNOS interaction were also tested. These molecules protect against NMDA but not NO mediated decreases in outgrowth. NMDA-R/PSD-95/nNOS may represent a target for the promotion of neuronal remodelling. Abstract: Glutamate and nitric oxide (NO) are important regulators of dendrite and axon development in the central nervous system. Excess glutamatergic stimulation is a feature of many pathological conditions and manifests in neuronal atrophy and shrinkage with eventual neurodegeneration and cell death. Here we demonstrate that treatment of cultured primary cortical rat neurons for 24 h with glutamate (500 μM) or N-methyl-d -aspartate (NMDA) (100–500 μM) combined with glycine suppresses neurite outgrowth. A similar reduction of neurite outgrowth was observed with the NO precursorl -arginine and NO donor sodium nitroprusside (SNP) (100 and 300 μM). The NMDA-receptor (NMDA-R) antagonists ketamine and MK-801 (10 nM) counteracted the NMDA/glycine-induced reduction in neurite outgrowth and the neuronal NO synthase (nNOS) inhibitor 1-[2-(trifluoromethyl)phenyl] imidazole (TRIM) (100 nM) counteracted both the NMDA/glycine andl -arginine-induced decreases in neurite outgrowth. Furthermore, targeting soluble guanylate cyclase (sGC), a downstream target of NO, with the sGC inhibitor 1H-[1, 2, 4]oxadiazolo[4, 3-a]quinoxalin-1-one (ODQ) (10 μM) also protected againstl -arginine-induced decreases in neurite outgrowth. Since the NMDA-R is functionally coupled to nNOS via the postsynaptic protein 95 kDa (PSD-95), inhibitors of the PSD-95/nNOS interaction were tested for their ability to protect against glutamate-induced suppression in neurite outgrowth. Treatment with the small-molecule inhibitors of the PSD-95/nNOS interface 2-((1H-benzo[d] [1, 2, 3]triazol-5-ylamino) methyl)-4, 6-dichlorophenol (IC87201) (10 and 100 nM) and 4-(3, 5-dichloro-2-hydroxy-benzylamino)-2-hydroxybenzoic acid (ZL-006) (10 and 100 nM) attenuated NMDA/glycine-induced decreases in neurite outgrowth. These data support the hypothesis that targeting the NMDA-R/PSD-95/nNOS interaction downstream of NMDA-R promotes neurotrophic effects by preventing neurite shrinkage in response to excess glutamatergic stimulation. The PSD-95/nNOS interface may be an attractive target for treating deficits in neuronal outgrowth and atrophy associated with excessive glutamatergic neurotransmission in neurodevelopmental and neurodegenerative conditions.